Pregnancy and malaria - Padilla, Armando (2015)
In 50 pregnant women with malaria attended at hospital Loreto, we encountered 27 cases by plasmodium falciparum and 213 by plasmodium vivax. Was malaria falciparum increased fetal death, prematurity, and RCIU and maternal mortality. We introduce a protocole of chemoprophylaxis to reduce the mentioned risks.